Canadian religious trends Secularization, polarization, or free-rider exclusion? - Dilmaghani, Maryam (2018)
Religiously unaffiliated Canadians have been persistently more likely to reside in the western provinces. In parallel, the degree of religiosity of the affiliates has been generally higher in the low affiliation provinces of the west. This pattern has led some scholars to characterize Canada as religiously polarized. However, in the literature, a quantitative measure of polarization is lacking. Moreover, religious polarization, a rather vividly debated characterization, is not by itself an explanation for the patterns. The present article, using the Canadian General Social Surveys of 1985 to 2011, contributes to the debate in three ways. First, this article establishes the robustness of the geographic discrepancies in unaffiliation rates and the degree of religiosity in Canada. Second, this study proposes and computes a quantitative measure of polarization. Finally the article explores the role of free-rider exclusion as an explanation for the patterns.
Keywords: Canada; déclin religieux; polarisation religieuse; religious decline; religious polarization; Secularization; Sécularisation